aboutsummaryrefslogtreecommitdiff
path: root/houdre/hw3.tex
blob: 21826f65f396e9bd0ad7d625275c3796fd6565aa (plain)
1
2
3
4
5
6
7
8
9
10
11
12
13
14
15
16
17
18
19
20
21
22
23
24
25
26
27
28
29
30
31
32
33
34
35
36
37
38
39
40
41
42
43
44
45
46
47
48
49
50
51
52
53
54
55
56
57
58
59
60
61
62
63
64
65
66
67
68
69
70
71
72
73
74
75
76
77
78
79
80
81
82
83
84
85
86
87
88
89
90
91
92
93
94
95
96
97
98
99
100
101
102
103
104
105
106
107
108
109
110
111
112
113
114
115
116
117
118
119
120
121
122
123
124
125
126
127
128
129
130
131
132
133
134
135
136
137
138
139
140
141
142
143
144
145
146
147
148
149
150
151
\newfam\rsfs
\newfam\bbold
\def\scr#1{{\fam\rsfs #1}}
\def\bb#1{{\fam\bbold #1}}
\let\oldcal\cal
\def\cal#1{{\oldcal #1}}
\font\rsfsten=rsfs10
\font\rsfssev=rsfs7
\font\rsfsfiv=rsfs5
\textfont\rsfs=\rsfsten
\scriptfont\rsfs=\rsfssev
\scriptscriptfont\rsfs=\rsfsfiv
\font\bbten=msbm10
\font\bbsev=msbm7
\font\bbfiv=msbm5
\textfont\bbold=\bbten
\scriptfont\bbold=\bbsev
\scriptscriptfont\bbold=\bbfiv

\def\Pr{\bb P}
\def\E{\bb E}
\newcount\qnum
\def\q{\afterassignment\qq\qnum=}
\def\qq{\qqq{\number\qnum}}
\def\qqq#1{\bigskip\goodbreak\noindent{\bf#1)}\smallskip}
\def\fr#1#2{{#1\over #2}}

\q2

$U$ and $V$ are pairwise independent, and $$\Pr(W=1) = \Pr(U=1)\Pr(V=1)
+ \Pr(U=-1)\Pr(V=-1)$$$$= ab + (1-a)(1-b) = ab + 1 -a -b + ab.$$
If $W$ is pairwise independent with $U$, $$\Pr(W) = \Pr(W=1|U=1) =
\Pr(V=1) = b = ab + 1 -a -b + ab$$$$\Longrightarrow 2b - 2ab = 1 -a =
2b(1-a)$$$$\Longrightarrow b = \fr12.$$

By a similar derivation, $a = \fr12.$ The three variables ${U,V,W}$ are
not independent. If they were, $\Pr(W=1|U=1) = b = \Pr(W=1|U=1|V=1) =
1.$ $b\neq1$, so the variables are not independent.

\q3

Both $X$ and $Y$ can be transformed into Bernoulli trials.  This
property is both necessary and sufficient for independence of a pair of
Bernoulli trials.
Necessity is shown by theorem 3.19, and it is sufficient because
$$\E(XY) = \Pr(X=1)\Pr(Y=1|X=1) = \Pr(X=1)\Pr(Y=1) = \E(X)\E(Y) \to
\Pr(Y=1) = \Pr(Y=1|X=1),$$
so this holds for $X$ and $Y$.

\q5

$$\Pr(Z=\min(X,Y)>z) = \Pr(X>z\cap Y>z) = \Pr(X>z)\Pr(Y>z),$$
by independence.

$$\Pr(X>z) = (1-p)^z \Longrightarrow \Pr(X>z)\Pr(Y>z) = (1-p)^z(1-r)^z =
(1-p-r+pr)^z.$$

$$\Pr(Z=z) = \Pr(Z>z-1) - \Pr(Z>z) = (1-p-r+pr)^{z-1} - (1-p-r+pr)^z =
(p+r-pr)(1-p-r+pr)^{z-1},$$
so $Z$ is a random variable following a geometric distribution with
parameter $p+r-pr.$

\q7

$$\E(X_1 + X_2 +\cdots+ X_N) = \sum_{n\in N} \Pr(N=n)\E(\sum_{i=1}^n
X_i).$$$$ \E(\sum_{i=1}^n X_i) = \sum_{\omega\in\Omega}\sum_{i=1}^n
\Pr(\omega)X_i(\omega) = \sum_{i=1}^n\sum_{\omega\in\Omega}
\Pr(\omega)X_i(\omega) = \sum_{i=1}^n\E(X_i) = n\mu.$$$$\Rightarrow
\E(X_1+\cdots+X_N) = \sum_{n\in N} \Pr(N=n)\mu = \mu\E(N).$$

\q12

When $i$ coupons have been collected out of $c$, the probability of
collecting a new coupon is $(c-i)/c$, so the probability of collecting a
new coupon on the $n$th trial (and not having collected one before) is
$((c-i)/c)*(1 - (c-i)/c)^{n-1}$. This is the geometric distribution on
parameter $(c-i)/c$. The expected value of a geometric distribution is
$1/p$ where $p$ is the parameter because
$$\E(X) = \sum_{i=1}^\infty i\Pr(X=i) = \sum_{i=1}^\infty \sum_{j=1}^i
pq^{i-1} = \sum_{j=1}^\infty \sum_{i=j}^\infty pq^{i-1}$$$$ =
\sum_{j=1}^\infty q^{j-1}\sum_{i=1}^\infty pq^{i-1} = \sum_{j=1}^\infty
q^{j-1} = (1/p)\sum_{j=1}^\infty pq^{j-1} = 1/p.$$

This means that the expected number of coupons collected before we have
a complete set is $\sum_{i=1}^c c/(c-i).$

% seriously needs to be proofread and checked for fit on the page

\q13

Suppose a string of $n$ coupons has $i$ unique coupons. This means $n-i$
duplicate coupons have been collected, each of which has a probability
$i/c$ of being collected instead of a new/unique coupon. The probability
of a unique coupon being chosen is shown to be $(c-k)/c$ in the question
above, which means there must be $i$ coupon collections of probabilities
$c/c, (c-1)/c, (c-2)/c, \ldots, (c-i-1)/c$. The product of these two is
$$\left({i\over c}\right)^{n-i}{c!\over(c-i)!c^i} =
{i^{n-i}c!\over(c-i)!c^n}.$$

$$\E(n) = \sum_{i=1}^n i{i^{n-i}c!\over(c-i)!c^n}$$

\q14

$X$ and $Y$ are binomial distributions for a fixed value of $N$.
With $p_N = \lambda^m\fr1{m!}e^{-\lambda},$ $p_X = {N\choose
k}p^kq^{N-k}$. Conditioning on $N,$
$$\Pr(X=k) = \sum_{i=1}^\infty \Pr(N=i){i\choose k}p^kq^{i-k} =
\sum_{i=1}^\infty \lambda^i\fr1{i!}e^{-\lambda}{i\choose k}p^kq^{i-k}
$$$$ =
{1\over k!}p^k\sum_{i=1}^\infty{e^{-\lambda}\lambda^iq^{i-k}\over(i-k)!}
= {1\over k!}p^k\lambda^ke^q
    \sum_{i=1}^\infty{e^{-q\lambda}(q\lambda)^{i-k}\over(i-k)!}
= {(p\lambda)^ke^q\over k!}
.$$
By a similar calculation, $\Pr(Y=k) = {(q\lambda)^ke^p\over k!}.$

To prove independence, $\Pr(X=x) = \Pr(X=x|Y=y) = \Pr(X=x|N=x+y)$, which
are $$\Pr(X=x) = {(p\lambda)^xe^q\over x!} = {{x+y\choose x}p^xq^y
\over \lambda^{x+y}e^{-\lambda}\fr1{(x+y)!}} = \Pr(X=x|N=x+y).$$
$$\lambda^{2x+y}e^q = {(x+y)!q^y(x+y)!
\over e^{-\lambda}y!}.$$

\qqq{3.37}
\def\var{\mathop{\rm var}\nolimits}
Let $A_i$ be the $i$th king/queen pair sitting next to eachother:
$$N = \sum_{i=1}^n 1_{A_i}.$$
This means
$$\E(N) = \E(\sum_{i=1}^n \E(1_{A_i}) = \sum_{i=1}^n\E(1_{A_i})
= \sum_{i=1}^n\Pr(A_i) = n\Pr(A_1),$$
by symmetry.
$\Pr(A_1) = 2/n$ because there are $n$ seats available to any given king
and $2$ possible seats to sit next to his queen, and $\E(N) = n(2/n)=2.$
$\var(N) = \E(N^2) - \E(N)^2,$ so we need $\E(N^2).$
$$\E(N^2) = \E\left(\left[\sum_i 1_{A_i}\right]^2\right)
= \E\left(\sum_i (1_{A_i}^2 = 1_{A_i}) + \sum_{i\neq
j}(1_{A_i}1_{A_j} = 1_{A_i\cap A_j})\right).$$

By symmetry, this is equal to
$$n\Pr(A_1) + n(n-1)\Pr(A_1\cap A_2),$$
and the second can be solved with conditional probability:
$$\Pr(A_1\cap A_2) = \Pr(A_1)\Pr(A_2|A_1) =
\fr2n\left(\fr1{n-1}\cdot\fr1{n-1} + \fr{n-2}{n-1}\cdot\fr2{n-1}\right)
= {2(2n-3)\over n(n-1)^2}.$$
The first term corresponds to the second queen sitting next to the first
couple and the second term is that not happening.

This leaves
$$\var(N) = \E(N^2) - \E(N)^2 = \left(2 + {2(2n-3)\over n-1}\right) -
4 = {2n-4\over n-1}.$$

\bye